2015
DOI: 10.4103/0973-1482.138193
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of salivary lactate dehydrogenase in oral leukoplakia and oral squamous cell carcinoma: A biochemical study

Abstract: The present salivary analysis for LDH enzyme reveals an overall altered salivary LDH enzyme level in OL and OSCC cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 13 publications
(21 reference statements)
5
39
0
1
Order By: Relevance
“…The comparison of salivary LDH levels between oral cancer and healthy subjects was statistically significant (p < 0.001). Our study finding was in agreement with the study done by Kallalli et al, 1 Lokesh et al, 8 Shetty et al, 16 Patel and Metgud, 4 and Joshi et al…”
supporting
confidence: 83%
See 4 more Smart Citations
“…The comparison of salivary LDH levels between oral cancer and healthy subjects was statistically significant (p < 0.001). Our study finding was in agreement with the study done by Kallalli et al, 1 Lokesh et al, 8 Shetty et al, 16 Patel and Metgud, 4 and Joshi et al…”
supporting
confidence: 83%
“…18 In our study, there was a significant difference in the salivary and serum LDH levels between oral leukoplakia and healthy controls (p = 0.001). Our results were in accordance with the study conducted by Patel and Metgud, 4 Pereira et al, 6 Rathore et al, 9 Joshi et al, 11 Shetty et al, 16 and Achalli et al 19 In our present study, while comparing among all the study groups, we found that serum and salivary LDH levels were significantly higher in oral cancer followed by OSMF and oral leukoplakia. Intergroup comparison for mean value of salivary LDH levels was significantly higher in oral cancer group than control, oral leukoplakia, and OSMF groups (p < 0.0001).…”
supporting
confidence: 83%
See 3 more Smart Citations